The style that was learned: large language models, imitation, and the ethics of literary influence - Nomvuselelo N. Nxumalo; Seroja Ainun Nadhifah (Asosiasi Relawan dan Pengelola Jurnal LPTNU (ARJUNU), 2026)
Background: Large language models have transformed literary imitation into a scalable practice, complicating distinctions among stylistic influence, textual reproduction, authorship, and ethical appropriation. Objective: This study examines how author-conditioned generation produces stylistic convergence, preserves or transforms source relations, and acquires ethical legitimacy under documented research conditions. Method: This study applies paired stylometry, intertextual reproduction auditing, and an ethical literary influence matrix to ten public-domain literary excerpts, ten controlled model outputs, five methodological documents, and seven contextual sources. Results: Stylometric comparison reveals graded convergence, with recognizable authorial cues coexisting with substantial divergence in sentence architecture and other distributed features. Reproduction auditing identifies low lexical overlap, no shared four-grams, no source-character or source-event transfer, and consistently high transformation across all pairs. Ethical coding classifies risk as low because sources are public domain, authors are deceased, prompts and exemplars are disclosed, and human control is documented. Implication: These findings indicate that literary resemblance should not be treated automatically as authorship, memorization, plagiarism, or infringement, but evaluated through layered textual and contextual evidence. Novelty: This study advances a multidimensional framework that theorizes learned style as mediated literary influence shaped by convergence, transformation, provenance, and accountable use across computational, literary, legal, and contemporary ethical domains.